Scrutinising well-known countermeasures against clone node attack in mobile wireless sensor networks. (1st January 2013) - Khan, Wazir Zada; Saad, Mohamad Naufal bin Mohamad; Aalsalem, Mohammed Y.
Wireless Sensor Networks (WSNs) are often deployed in unattended environments where an adversary can easily physically capture and compromise sensor nodes. She then creates replicas of the compromised nodes instigating further attacks by spreading these replicas over the network, incurring serious damages to the network, so these replicas should be detected as early as possible. Most of the previous research efforts on detecting replica node attacks adopt static network models which are not suitable for mobile WSNs. In mobile WSN, sensor nodes are freely and randomly roaming all the time and they do not have any fixed neighbour to communicate with because these mobile nodes meet with one another occasionally and in an unpredictable manner. In this paper, we have surveyed all the existing solutions proposed so far for the detection of replica or clone nodes in mobile WSN by comparing them comprehensively and pointing out their drawbacks and shortcomings.